Time variations of the relationships between the North Atlantic Oscillation and European winter temperature and precipitation - Beranová, R.; Huth, R. (Studia Geophysica et Geodaetica)
The degree of stationarity of relationships between the NAO index and long European temperature and precipitation series in winter is quantified by running correlations with a time window of 31 years at 29 and 27 stations in Europe, respectively. They indicate major nonstationarities in the NAO-to-surface climate relationships at most stations. The temporal course most common for correlations with temperature is a slight change prior to about 1950, followed by an increase; for precipitation, a typical course is a decrease in the first half of the 20th century, followed by an increase. The temporal variations in correlations do not result from the presence of trends in the time series. The periods of high correlations with temperature are accompanied with an eastward shift of both NAO action centres; the eastward shift is thus at least partly responsible for the time variations in correlations.